2017
DOI: 10.1111/jan.13253
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of evidence relating to clinical supervision for nurses, midwives and allied health professionals

Abstract: Despite insufficient evidence to directly inform the selection and implementation of a framework, the limited available evidence can inform the design of a new model of clinical supervision for UK-based midwives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 38 publications
1
54
0
5
Order By: Relevance
“…While I acknowledge that poorly designed studies can be well reviewed/reported and well‐designed studies can be poorly reviewed/reported, these findings support those from other careful review studies (see, e.g. Pollock et al., ).…”
supporting
confidence: 65%
“…While I acknowledge that poorly designed studies can be well reviewed/reported and well‐designed studies can be poorly reviewed/reported, these findings support those from other careful review studies (see, e.g. Pollock et al., ).…”
supporting
confidence: 65%
“…We devised a method for judging the comprehensiveness of the description of the method or approach to involvement, given that there are no standardised tools for such a task. Criteria for categorising the comprehensiveness of the description provided within papers were developed, adapted from Pollock [ 28 ]. Initially, two reviewers (AP, CS) assigned these criteria independently for a random sample of 20% of papers identified from step 1 of searching; this was 42 of 210 papers.…”
Section: Methodsmentioning
confidence: 99%
“…small group discussions) and/or experiential learning (e.g. role-play, feedback) (Spence et al 2001 ; Hoge et al 2011 ; Pollock et al 2017 ). The duration of supervision training ranges from one-off, short-term interventions (such as a 2-day workshop) to extended-duration interventions over many months that are punctuated by mini-interventions such as monthly supervision sessions (Spence et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%